Analysis of The Impact of Space Application Patterns in Placing the Location of Economic Activities Through the Conversion Mechanism of Raw Land Field Land Conversion - Sukiptiyah Sukiptiyah; Ernan Rustiadi; Akhmad Fauzi; Baba Barus (Publikasi Indonesia, 2022)
Conversion of agricultural land into built-up land is a regional economic development mechanism, where to increase Gross Domestic Product can be done by allocating the widest possible pattern of space designation